Filosofisk Leksikon - Pálfi, Loránd-Levente; Lange, Andreas Møller (LexicoNordica, 2009)
Anmeldt værk: Filosofisk Leksikon. 1. udgave, 1. oplag. København: Gyldendal 2008. 528 sider, ill., indb. Kr. 499,-